Maternal morbidity and mortality from severe sepsis: a national cohort study. Issue 8 (23rd August 2016) - Acosta, Colleen D; Harrison, David A; Rowan, Kathy; Lucas, D Nuala; Kurinczuk, Jennifer J; Knight, Marian
Abstract : Objectives: To describe the incidence, characteristics and risk factors for critical care admission with severe maternal sepsis in the UK. Design: National cohort study. Setting: 198 critical care units in the UK. Participants: 646 pregnant and recently pregnant women who had severe sepsis within the first 24 hours of admission in 2008–2010. Primary and secondary outcome measures: Septic shock, mortality. Results: Of all maternal critical care admissions, 14.4% (n=646) had severe sepsis; 10.6% (n=474) had septic shock. The absolute risk of maternal critical care admission with severe sepsis was 4.1/10 000 maternities. Pneumonia/respiratory infection (irrespective of the H1N1 pandemic influenza strain) and genital tract infection were the most common sources of sepsis (40% and 24%, respectively). We identified a significant gradient in the risk of severe maternal sepsis associated with increasing deprivation (RR=6.5; 95% CI 4.9 to 8.5 most deprived compared with most affluent women). The absolute risk of mortality was 1.8/100 000 maternities. The most common source of infection among women who died was pneumonia/respiratory infection (41%). Known risk factors for morbidity supported by this study were: younger age, multiple gestation birth and caesarean section. Significant risk factors for mortality in unadjusted analysis were: age ≥35 years (unadjusted OR (uOR)=3.5; 95% CI 1.1 to 10.6), ≥3 organ system dysfunctions (uOR=12.7; 95% CI 2.9 to 55.1), respiratory dysfunction (uOR=6.5; 95% CI1.9 to 21.6), renal dysfunction (uOR=5.6; 95% CI 2.3 to 13.4) and haematological dysfunction (uOR=6.5; 95% CI 2.9 to 14.6). Conclusions: This study suggests a need to improve timely recognition of severe respiratory tract and genital tract infection in the obstetric population. The social gradient associated with the risk of severe sepsis morbidity and mortality raises important questions regarding maternal health service provision and usage.